-The rules of the jurisprudential judgments affected by weather conditions - A study of the applied principles in the worship of purity - Al - Shaibani, Hassan Mouloud Hassan; Yahya, Mohamed Zinni; Qasim, Dato Mohammed Show Arif Bin Mohammed (Journal of Humanities & Social Sciences, 2017)
Islamic shariah is the core of research and study. However, it comes after worship and obedience that bring us closer to Allah Almighty. One may go through some weather conditions that affect performing various ibadah (worships of Allah). This paper aims to examine these cases tracing the opinions of the scholars from the authentic resources of the four-famous school of thoughts (mathahib) implementing the inductive and deductive approaches. Hence, the paper is entitled “Rules of jurisprudence affected by weather conditions: A foundational applied study of purification (tahaarah)”. The problem addressed in this paper is to set jurisprudential rules that control performing of worships during weather changes and how these rules may change due to the weather changes. The paper provides a definition to the jurisprudential rules to distinguish them from the jurisprudential principles. The paper also examines the concept of weather conditions and their relationship with the Shariah law. Examples of some jurisprudential rules related to the worship of purification are mentioned as this paper cannot examine all the rules. The paper highlights the significance of this study, its problem, and objectives. The paper concludes that the rules of purification (tahaarah) affected by weather conditions, which amounted to seventeen rules however the paper can only fit to three of them, including: the winds (what the wind throws, which is unavoidable, is permissible), hailstones (it is also pure in itself and it is a purifier), and the cold weather rules (taking off gloves and wiping). The paper traces the opinions of the scholar and and selects the preferable opinion (rajih).
Keywords: jurisprudential controls; purity; wind; rain; snow; hail